Nanotubes TiO2 supported Pt catalyst for selective electrocatalytic oxidation of glycerol to glyceric acid. Issue 17 (1st September 2020) - Qin, Guoxu; Wang, Xinyun; Wan, Xinjun; Chen, Dong; Qiu, Bo
ABSTRACT: Highly ordered nanotubes titanium dioxide (NTs-TiO2 ) array was fabricated and used as the support of Pt nanoparticles for the selective aqueous phase of glycerol (GLY) electrooxidation. The structure and morphology of the NTs-TiO2 /Pt were characterized by X-ray diffraction, scanning electron microscope, transmission electron microscope, etc. The electrooxidation GLY properties of NTs-TiO2 /Pt were investigated by cyclic voltammetry, linear sweep voltammetry, and accelerated service life test. The results show that, compared with bulk Pt and nano-TiO2 /Pt, the NTs-TiO2 /Pt have the highest service life and electrooxidation activity and selection for GLY. At the reaction condition of 1.2 V potential, the NTs-TiO2 /Pt catalyst afforded 67.1% selectivity for the glyceric acid.